2018
DOI: 10.1007/s40121-018-0200-7
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Bactericidal and Virucidal Efficacy of Povidone-Iodine Gargle/Mouthwash Against Respiratory and Oral Tract Pathogens

Abstract: IntroductionRecent virus epidemics and rising antibiotic resistance highlight the importance of hygiene measures to prevent and control outbreaks. We investigated the in vitro bactericidal and virucidal efficacy of povidone-iodine (PVP-I) 7% gargle/mouthwash at defined dilution against oral and respiratory tract pathogens.MethodsPVP-I was tested against Klebsiella pneumoniae and Streptococcus pneumoniae according to bactericidal quantitative suspension test EN13727 and against severe acute respiratory syndrome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
357
0
19

Year Published

2020
2020
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 358 publications
(385 citation statements)
references
References 32 publications
9
357
0
19
Order By: Relevance
“…At present there is no available evidence addressing the effects of commonly used antimicrobial mouth rinses on COVID 19. Hence, this recommendation could be based on the fact that gargling has been reported to decrease the viral load and spread by removing oropharyngeal protease and associated viral replication [29]. In addition, mouthwashes containing agents with anti-viral activity such as povidone-iodine have exhibited effectiveness against various respiratory viruses [30,31].…”
Section: Discussionmentioning
confidence: 99%
“…At present there is no available evidence addressing the effects of commonly used antimicrobial mouth rinses on COVID 19. Hence, this recommendation could be based on the fact that gargling has been reported to decrease the viral load and spread by removing oropharyngeal protease and associated viral replication [29]. In addition, mouthwashes containing agents with anti-viral activity such as povidone-iodine have exhibited effectiveness against various respiratory viruses [30,31].…”
Section: Discussionmentioning
confidence: 99%
“…2. Using 0.23% povidone-iodine mouthwash for at least 15 s before the procedure can reduce the viral load in the patient's saliva (Eggers et al, 2018).…”
Section: Treatment Considerationsmentioning
confidence: 99%
“…0.001%). A detailed review of its virucidal activity against a wide range of common viruses, including SARS-CoV and MERS-CoV coronaviruses, is beyond the scope of this article [6]. As a word of caution, in vitro studies using 10% and 5% PVP-I have demonstrated cilotoxicity on human respiratory cells [7].…”
Section: Letter To the Editormentioning
confidence: 99%
“…However other investigations demonstrate continued virucidal effects of diluted PVP-I concentrations, without evidence of respiratory cilia toxicity, diminished olfactory function, or changes in mucosal appearance [8]. In vitro studies of 0.23% PVP-I mouthwash (1:30 dilution) can inactivate both SARS-CoV and MERSCoV following a 15-second exposure [6]. Though rare, prolonged use of topical 10% PVP-I solution (weeks-months) may increase the risk of iodine toxicity [9].…”
Section: Letter To the Editormentioning
confidence: 99%